Baznas Bogor City Strategy in Empowering the Dhuafa Through the Bogor Berkah Program - Efrita Norman; Zulficar Ismail; Abdul Husenudin; Enah Pahlawati; Rio Kartika Supriyatna (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Zakat is one of the pillars in the Islamic economy which is a pillar of the Islamic religion, the importance of zakat in the economy is why in the Qur'an zakat is always juxtaposed with prayer, there are even 29 words zakat which are always juxtaposed with prayer, because zakat is meritorious in Community economic empowerment must be managed properly by amil zakat, in this context is BAZNAS Bogor City. The purpose of zakat itself is not only to help asnaf but also to make mustahiq become muzakki, therefore the distribution of zakat funds must be right on target so that this goal is achieved. This study aims to determine the determination of recipients of zakat funds distributed by BAZNAS Bogor City through one of its programs, namely Bogor Berkah, whether with this program the zakat asnaf group is helped and this study takes the object of ta'lim majlis. The approach used in this research is descriptive qualitative with SWOT analysis approach, IFAS (Internal Strategic Factor Analysis Summary) and EFAS (External Strategic Factor Analysis Summary). The results of this study indicate that in determining the receipt of zakat funds distributed by BAZNAS Bogor City through the Bogor Berkah program is the majlis ta'lim criteria which have small or medium business groups. and with this program there are not a few ta'lim majlis that empower their congregations of ta'lim majlis. Keywords: zakat, bogor blessing program, empowerment of dhu'afa